Kim są „superiores barbari” w Vita Marci Antonini (14.1) - Malinowski, Gościwit (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
The phrase Profecti tamen sunt paludati ambo imperatores et Victualis et Marcomannis cuncta turbantibus, aliis etiam gentibus, quae pulsae a superioribus barbaris fugerant, nisi reciperentur, bellum inferentibus was translated by David Magie in the Loeb Classical Library series as “Clad in the military cloak the two emperors finally set forth, for now not only were the Victuali and Marcomanni throwing everything into confusion, but other tribes, who had been driven on by the more distant barbarians and had retreated before them, were ready to attack Italy if not peaceably received.”
Keywords: superiores barbari; Historia Augusta; wojny markomańskie; Marek Aureliusz; Markommanowie; plemiona germańskie; przekłady